Adherence model to cervical cancer treatment in the Covid-19 era (Baghdad Science Journal, 2023)
Cervical Uterine Cancer is a disease that explains the vulnerability in which women are in terms of reproductive health with an impact on occupational health and public health, even when in Mexico the prevalence rate is lower than the other member countries of the OECD, its impact on Human Development and Local Development shows the importance that the disease have in communities more than in cities where prevention policies through check-ups and medical examinations seem to curb the trend, but show the lack of opportunities and capacities of health centers in rural areas.   To establish the reliability, validity, and correlations between the variables reported in the literature with respect to their weighting in a public hospital. A non-experimental, cross-sectional and exploratory study was carried out with a non-probabilistic selection of 104 patients from a public hospital in the State of Mexico. The Scale of Psychosocial Variables Determinants of Adherence to Treatment of Cervical Uterine Cancer was constructed. From a structural model, it was demonstrated the adjustment of the trajectories of determining relationships in which knowledge influenced the behavior of adherence to treatment. The limits of the design, sampling and analysis of the study are noted and it is recommended to include organizational and psychological variables supported by theories of organizations and theories of personality.